The seizure semiology consistent with frontal lobe symptomatogenic zone in children - Öztoprak, Ülkühan; Yalnızoğlu, Dilek; Oğuz, Kader Karlı; Ergun, Eser Lay; Söylemezoğlu, Figen; Bilginer, Burçak; Akalan, Nejat; Topçu, Meral; Turanlı, Güzide (The Turkish Journal of Pediatrics, 2016)
The aim of this study is to analyze the seizure semiology consistent with frontal lobe symptomatogenic zone in childhood. We analyzed 549 videotaped seizures from 79 patients (mean age 9.9 ± 3.8 years). Magnetic resonance imaging was normal in 30 patients. The seizures in the time interval of 10 p.m. to 6 a.m. were considered as nocturnal. The mean number of seizures per patient was 6.8 ± 7.3. The mean seizure duration was 25.7 ± 26.9 sec; postictal confusion was 27 ± 16.1 sec (7-92 seconds). The seizures were observed in sleep with a rate of 56.8%; 43.1% of them were during wakefulness. Overall 50.4% of the seizures occured during night-time sleep. Tonic seizure (77.2%) was the most frequent simple motor seizure. Versive seizures were the second most frequent type of simple motor seizure (26.7%). Clonic seizures were 17.7%, complex motor seizures were 20.5%, and dialeptic seizures were 3% of all the seizures. Epileptic spasm, myoclonic seizures, aphasia, and akinetic semiologies were not observed. Vocalization was observed in 16% of the seizures. Frontal lobe seizures in childhood have a short duration, occur frequently, especially during night time sleep, and have a brief postictal period. Tonic semiology, versive semiology are the most frequent seizure semiologies; hypermotor and secondary generalized tonic clonic seizures and vocalizations are observed less in children compared to adults.
Keywords: childhood; frontal lobes; seizure semiology